الأسرة الليبية المتكونة عبر المجتمع الافتراضي الخصائص، والتحديات "دراسة على عينة من الأزواج والزوجات بمواقع التواصل الاجتماعي، الفيس بوك، ماسنجر" - الزياني, نجلاء فتحي (Scientific Journal of University of Benghazi, 2021)
This study of families created through virtual society aims to determine the reality of these families in terms of identifying the characteristics of the couples who make up these families, the mechanisms of how they initially met, the motives of choosing this type of relationship for marriage and the formation of the family, the challenges facing the husband and wife who meet online, and the extent of the cohesion of the family formed through the virtual society. The study was based on the descriptive method and the sample of the study consisted of 30 individuals selected by the method of deliberate sample through social networking sites, such as Facebook and Messenger. An electronic form was used in the collection of the study data, and this paper was used to display the results of the study. The couples in families formed through the virtual society are characterized by the fact that they belong to a young age group, have high incomes, are from urban environments, and have university and higher education levels. Additionally, the people who met online made the decision to get married quickly, and the results of the study also highlighted the length of the marriages. The results of the study showed that Facebook and Messenger are the most common means of meeting and that the motives behind using this method of marriage are the ease of making acquaintances, choice and differentiation. Furthermore, it suits individuals with independent personalities, who reject traditional methods of meeting spouses. This method enables the freedom of expression of opinions, feelings and desires, and was imposed by the nature of development and change in society.